A Retrospective Research of the Characteristic of Hypertriglyceridemic Pancreatitis in Beijing, China. (5th January 2016) - Tai, Wei-Ping; Lin, Xiang-Chun; Liu, Hong; Wang, Cang-Hai; Wu, Jing; Zhang, Neng-Wei; Chen, Wei
Abstract : Aim . To investigate the characteristic of hypertriglyceridemic- (HTG-) induced pancreatitis (HTG pancreatitis). Methods . We reviewed 126 cases of HTG pancreatitis and 168 cases of biliary pancreatitis as control. Results . The HTG group mean age was younger than biliary group. The number of females was a little higher than males in both groups. There were 18 cases that were recurrent in HTG group and 11 in billiary group. The mean hospitalization times were 13.7 ± 2.6 and 11.2 ± 2.3 days in two groups. Six patients received apheresis in HTG group. The proportion of severe AP was 31.0% and 26.2%, mortality 1.6% and 1.2%, comorbidity of diabetes mellitus (DM) 20.6% and 6.5% in two groups. The number of complications of gastrointestinal (GI) bleeding, sepsis, and multiple organ dysfunction syndrome (MODS) in HTG group and biliary group was 1, 1, and 2 versus 4, 12, and 4. Conclusions . The proportion of recurrent and severe AP and comorbidity of DM of HTG group was higher than billiary group. The proportion of the complications of GI bleeding, sepsis, and MODS of HTG group was less than biliary group. Apheresis could effectively reduce serum TG levels soon. There was no significant difference of the mortality between two groups.